English English - Azmi Muhammad Ilyas; Sri Dewi Nirmala; Zaynab Bolanle Raji-Ellams (Universitas Negeri Surabaya, 2025)
A decline in elementary student’s self-efficacy has become increasingly visible in recent years, which caused learning loss and reduced student’s confidence in completing academic tasks independently. Strengthening self-efficacy is essential because it influences participation, persistence, and achievement. This study investigates the effectiveness of the Discovery Learning model in improving student’s self-efficacy in elementary science learning. A descriptive qualitative approach supported by descriptive quantitative data was employed, involving 47 sixth-grade students across three learning sessions designed according to the Discovery Learning stages. Data were collected through participatory classroom observation, a Likert-scale self-efficacy questionnaire administered before and after learning, unstructured interviews, and field notes. Observation results showed a progressive increase in self-efficacy across learning stages, particularly during phases requiring investigation, discussion, verification, and presentation. Questionnaire results indicated an average improvement of 23 percentage points across five self-efficacy indicators, with the highest gains in social interaction ability and willingness to take risks. Interview data confirmed that students felt more confident due to meaningful field experiences, peer support, and opportunities to present findings. Triangulated data suggest that Discovery Learning effectively enhances elementary student’s self-efficacy by providing direct and socially interactive learning experiences. These findings highlight the potential of Discovery Learning as a pedagogical model to reinforce confidence and independence in science learning.